ANALISIS AUDIT EXPECTATION GAP PADA SEKTOR PUBLIK (Studi Empiris pada Pemerintah Provinsi Banten) - Nasrullah, Nasrullah; Ismail, Tubagus; Yazid, Helmi (JURNAL RISET AKUNTANSI TIRTAYASA, 2017)
This study aims to determine the effect of accounting knowledge, qualifications and work experience of auditors on the audit expectation gap and audit expectation gap in the quality of the audit report. In addition, this study investigated the mediating role of audit expectation gap. Structured questionnaire was distributed randomly to 86 auditee of 43 Local Government Organizations in Banten Province. A total of 70 questionnaires of the completed and analyzed.  The sample in this study were taken by using the data collection method called purposive sampling. The criteria of the sample in this study is the fourth echelon officials in charge of finance and reporting. The data obtained were analyzed by using PLS analysis technique (Partial Least Square) through the PLS software. Moreover, to test the hypothesis of the mediating, Sobel test was used to examine the relationship existing intervening variables in the hypothesis. The results showed that accounting knowledge no effect in reducing the gap expectations of the audit, and the audit expectation gap can not mediate accounting knowledge on the quality of the audit report. Auditor's qualifications and work experience effect in reducing the gap expectations of audit and audit expectation gap may mediate the effect of qualifications and work experience of the quality of the audit report. Review findings have implications for understanding change accounting knowledge auditee against the auditor in the audit process is very important and the importance of the recruitment of auditors who have the educational background of accounting.Keywords    : Accounting knowledge, accounting qualification, worok experience,audit expectation gap and quality of audit report.